Rydbergovi atomi - Čoko, Urban (Matrika, 2021)
Rydberg atoms are atoms with one or more electrons, excited to high principal quantum number n. First part of the article deals with the properties of a Rydberg hydrogen atom and expands the description to alkali metal atoms. Second part of the article uses the theory derived in the first part to explain the principles of electric field sensing with Rydberg atoms.
Keywords: atomic physics; fizika atomov; Rydberg atoms; Rydbergovi atomi